ANALISIS MAJAS DALAM LIRIK LAGU â€œKU KIRA KAU RUMAHâ€ KARYA AMIGDALA - nadhifah, rifa nurul (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This article aims to discover and figure of speech to describe what just what is contained in the lyrics of the song "I Guess You're Home" by Amigdala of the indi band in Indonesia who came from the city of Bandung. Problems in this study include analysis of aspects of the composition that make the lyrics of this song interesting to study. Researchers see the narrative or drama of human romance with a polemic in the lyrics of the song "Ku Kira Kau Rumah" which is packaged in the form of figurative words. Song lyrics usually contains feelings, emotions, thoughts, which pour in writing, in the lyrics of the song writer will use language that is beautiful that can be enjoyed by the audience and writers too often makes curious about the choice of words used in the song. As if it is a certain code that wants to be conveyed to the listener. The method used by researchers is the Stylistic method. This method aims to analyze the style and more refers to the style of language. The analytical technique used in the lyrics of the song "Ku Kira Kau Rumah" uses a technique of majas analysis. This technique aims to select certain words in accordance with the intent of the writer or speaker in order to obtain the beauty aspect. The results of stylistic research on the lyrics of the song "Ku Kira Kau Rumah" by Amigdala contain two types of majors, they are comparative and repetitive forms.